Marcas blancas, valor percibido y la lealtad en el sector retail. - Márquez Peñaloza, Evelyn; Leiva-Riofrio, Gissella; Shagui González, Joyce; Sánchez González, Irene (My University, 2021)
Analyze the perceived value of the white brands consumer and its influence on loyalty and the construction of brand capital in the retail sector. Descriptive method with a transversal approach, a structured survey is applied to a sample of 138 department store consumers. The perceived value of the consumer on white brands positively influences brand loyalty and capital. Retailers that engage in marketing strategies that communicate retailer engagement have positive results on brand equity.
Analizar el valor percibido del consumidor de marcas blancas y su influencia en la lealtad y la construcción del capital de marca en el sector retail. Método descriptivo de enfoque transversal, se aplica una encuesta estructurada a una muestra de 138 consumidores de tiendas departamentales. El valor percibido del consumidor sobre las marcas blancas, influye positivamente sobre la lealtad y el capital de marca. Los minoristas que involucran estrategias de marketing que comuniquen el compromiso del minorista, tienen resultados positivos en el capital de marca.
Keywords: MARCAS BLANCAS; MARKETING; LEALTAD; VALOR PERCIBIDO; CAPITAL DE MARCA